Manajemen pemasaran: pemasaran elektronik - hidayah, anadia (Maliki Interdisciplinary Journal, 2025)
Electronic marketing (e-marketing) has revolutionized the global business landscape. With the rapid development of digital technology, companies now have wider access to reach consumers throughout the world. This research aims to analyze the important role of electronic marketing in the context of modern business, as well as identifying the challenges and opportunities faced by business people in implementing effective electronic marketing strategies. Through literature reviews and case studies, this research reveals that electronic marketing offers a variety of significant benefits, such as increased efficiency, personalization of marketing messages, and more accurate performance measurement. However, on the other hand, there are a number of challenges that need to be overcome, including increasingly fierce competition, dynamic changes in consumer behavior, and data security. This research concludes that success in electronic marketing depends on several key factors, including a deep understanding of digital consumer behavior, appropriate use of technology, and close integration between electronic marketing strategies and the company's overall business strategy. Apart from that, companies also need to pay attention to ethical and legal aspects in carrying out electronic marketing activities.